English Language Training for Academic Purposes (EAP) provided to students in preparing scholarly works - Gurusinga, Mona Fitri (INSTITUT KESEHATAN DELI HUSADA, 2026)
Public speaking in The ability to speak English is crucial. for students within the globalization era. However, many students still face challenges in terms of confidence, pronunciation, and delivering ideas efficiently. Through English public speaking instruction at SMA Negeri 1 Deli Tua, this community service program seeks to boost students' self-esteem. The method used is a participatory training approach, including material presentation, practice sessions, simulations, and evaluation. The participants were students interested in improving their English-speaking skills. The findings indicate that pupils' confidence has increased., fluency, and ability to present ideas systematically. Additionally, students responded positively to the interactive and communicative training methods. Therefore, English public speaking training can be an effective strategy to improve students' communication competence.